Juvenile hybrid white-collar delinquency: an empirical examination of various frauds - Schoepfer, Andrea (Criminology, criminal justice, law & society, 2017)
With recent technological advances, juveniles now have more opportunities to engage in certain types of hybrid white-collar crime such as credit card fraud, identity theft, general fraud, intellectual property crimes, and financial/bank fraud, yet they are largely ignored in white-collar crime research due to offender- and opportunity-based definitions of the phenomenon. Using data from the Florida Department of Juvenile Justice, the current paper examines various aspects of this recently acknowledged variety of offending behavior among juveniles. Results indicate that significant differences exist between hybrid white-collar delinquents and conventional crime delinquents in various factors identified in the literature relating to deviant/criminal behavior. Theoretical implications and future research directions are also discussed.